UPRATING OF FRANCIS WATER TURBINE WITH HEAD OF 42 M AND DISCHARGE OF 0.585 M3/S WITH VARIOUS NACA PROFILE FOR RUNNERâS BLADE - Kiasatina, Nabilah
Indonesia's electricity consumption is expected to triple by 2030. The solution to overcome the increasing electricity demand is to use renewable energy for electricity generation. Water is the largest potential renewable energy source in Indonesia. However, the utilization has not been maximized. The solution to increase energy utilization in water is by increasing performance, namely efficiency and output power at the plant or known as uprating. In this Final Project, uprating was carried out by creating a new design on Francis type water turbine’s runner with discharge data of 0.585 m3 / s, 42 m head, and 1000 rpm rotational speed which then simulated to obtain efficiency and output power that approached the actual state. The parameters changed for this uprating are the guide vane opening angle, number of blades on runner and cross-section profile of blade varied in three NACA airfoil profiles, NACA 0006, NACA 0008 and NACA 0012. Uprating is said to be successful if the uprated turbine’s performance exceeds existing turbine’s performance. Based on the results of modeling, simulation, and analysis, the new runner’s geometry with 15 runner’s blades was obtained and the thickness obtained by the NACA 0008 profile that was able to produce the best efficiency was 90.87% with an output power of 138.96 kW on the 16° of guide vane opening. Therefore, the NACA 0008 airfoil profile was chosen for the uprated runner’s blade. While the highest output power of this new turbine is 188.40 kW with an efficiency of 82.22% on the 30° of guide vane opening.